Anti-Vibrio Indole-Diterpenoids and C-25 Epimeric Steroids From the Marine-Derived Fungus Penicillium janthinellum - Guo, Xing-Chen; Xu, Lan-Lan; Yang, Rui-Yun; Yang, Meng-Yue; Hu, Lian-Dong; Zhu, Hua-Jie; Cao, Fei (Frontiers in Chemistry, 2019)
A systematic chemical exploration of the marine-derived fungus Penicillium janthinellum led to the isolation of four indole-diterpenoid derivatives (1–4), including new penijanthines C and D (1 and 2), and a pair of new steroidal epimers, penijanthoids A and B (5 and 6). The calculated ECD spectra and Snatzke's method for the new compound 1 were carried out to determine its absolute configuration. The absolute configuration of 3 was established by X-ray diffraction and calculated ECD methods for the first time. DP4plus approach was used to elucidate the absolute configurations of the C-25 epimeric steroids 5 and 6. 25-Epimeric 5 and 6 represent the first examples of steroids forming a five-membered lactone between C-23 and C-27 from marine fungi. Compounds 1, 2, 5, and 6 displayed significant anti-Vibrio activity (Minimum inhibitory concentration, MIC values ranging from 3.1 to 50.0 μM) against three pathogenic Vibrio spp.